2015
DOI: 10.1371/journal.pone.0144721
|View full text |Cite
|
Sign up to set email alerts
|

Differences of Intrasession Reproducibility of Circumpapillary Total Retinal Thickness and Circumpapillary Retinal Nerve Fiber Layer Thickness Measurements Made with the RS-3000 Optical Coherence Tomograph

Abstract: PurposeTo evaluate the intrasession reproducibility of various thickness parameters used to diagnose and follow-up glaucoma, in particular circumpapillary total retinal thickness (cpTR) provided by the RS-3000 optical coherence tomograph (OCT).MethodsFifty-three healthy eyes of 28 subjects underwent three consecutive imaging with the RS-3000 Advance OCT (NIDEK, Aichi,Japan) to evaluate the intrasession reproducibility of circumpapillary total retinal thickness (cpTR), circumpapillary retinal nerve fiber layer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…The retinal structure in eyes with ONH has been studied using optical coherence tomography (OCT) 8 9 10 and histopathologic analysis 2 11 12 , with the focus on the ganglion cell layer (GCL) and retinal nerve fiber layer (RNFL). Pathological studies have reported a significant reduction in the thicknesses of the GCL and RNFL in eyes with ONH 2 11 12 , and these findings have been confirmed non-invasively in vivo by OCT measurements 8 9 10 with excellent reproducibility 13 .…”
mentioning
confidence: 76%
“…The retinal structure in eyes with ONH has been studied using optical coherence tomography (OCT) 8 9 10 and histopathologic analysis 2 11 12 , with the focus on the ganglion cell layer (GCL) and retinal nerve fiber layer (RNFL). Pathological studies have reported a significant reduction in the thicknesses of the GCL and RNFL in eyes with ONH 2 11 12 , and these findings have been confirmed non-invasively in vivo by OCT measurements 8 9 10 with excellent reproducibility 13 .…”
mentioning
confidence: 76%
“…The thickness of the combined inner retinal layers, known as the ganglion cell complex (GCC), includes the retinal nerve fiber layer, ganglion cell layer, and inner plexiform layer 32 . Moreover, circumpapillary retinal nerve fibers (cpRNFLs) were also measured 33 . A glaucomatous VF loss was defined as MD and PSD with p<0.05, and a cluster in the pattern standard deviation plot of at least 3 points with p<0.05, one of each with p<0.01, not contiguous with the blind spot and not crossing the horizontal midline.…”
Section: Study Populationmentioning
confidence: 99%
“…When these two parameters were combined, the glaucoma detection rate increased to 83%. In previous investigations, the cpTR thickness exhibited a high reproducibility,[24] and when using the Spectralis OCT, had an even higher diagnostic accuracy for glaucoma than the cpRNFL thickness. [30] In the current investigation, the AUROC for cpTR thickness was higher than that of the cpRNFL thickness although the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 98%
“…To further improve the diagnostic accuracy of SD-OCT technology, various novel SD-OCT parameters for their clinical usefulness in glaucoma diagnostics were investigated. [202122232425] Recently, Kita et al . have shown that the reproducibility of the circumpapillary total retina (cpTR) thickness is higher than that of the cpRNFL thickness[24] and that the ratio of mGCC thickness to macular outer retinal thickness (G/O ratio) has significantly higher diagnostic accuracy than cpRNFL thickness in Japanese eyes.…”
mentioning
confidence: 99%
See 1 more Smart Citation